Cu(II) complex with thiosemicarbazone of glyoxylic acid as an anion ligand in a polymeric structure - YALÇIN, BAHATTİN (ELSEVIER SCIENCE BV, 2019)
A new complex of Cu(II), the composition Cu(C3H7N3O4S)center dot H2O, the reaction of thiosemicarbazone glyoxylic acid with copper nitrate in an aqueous medium was synthesised. X-ray diffraction analysis established the composition of the complexes was studied by IR, UV electronic absorption and EPR spectroscopy, and thermogravimetry. Thermogravimetry shows five stages of decomposition in the temperature range 90-990 degrees C. The magnetic susceptibility of the complex is studied. The value of mu(eff) for the complex is 1.76 BM, which is close to the value of one unpaired electron (1.73 BM). The ligand coordinates with the metal atom and consists of monoanionic Cu(C3H7N3O4S)center dot H2O polymeric complex connected by Cu-N bonds with neighbouring molecules. The metal centre coordinates with the oxygen of carboxylic, sulfur of thiolic and nitrogen of the azomethine group. The X-ray data and ESR spectra specify a distorted square pyramidal environment around Cu(II) ion. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Thiosemicarbazones; Cu-complex; Crystal structure; COPPER(II) COMPLEXES; BIOLOGICAL-ACTIVITY; SPECTROSCOPIC CHARACTERIZATION; COORDINATION-POLYMER; PYRUVIC-ACID; BASE; CRYSTAL